Diode Laser Frenectomy (Clinical documentation): Case Report. - Darya Alhaidary; Noor Othman; Rayan Hadi; Elaf Ayad (Erbil Dental Journal)
Introduction: As an alternative to conventional dental procedures, laser surgery has grown in favor recently. Among other laser types, diode lasers have attracted significant interest in the field of oral soft tissue surgery.